The Effect of Giving Fermented Milk Starter Lactococcus lactis D4 Dadih on Obstructive Jaundice: An In Vivo Study - Syahriandra; M. Iqbal Rivai; Irwan; Ade Sukma; Tofrizal (HM Publisher, 2022)
Background: Every 1 person out of 3 people with obstructive jaundice will die from complications of obstructive jaundice. The absence of bile salts causes the loss of the protective layer of the intestinal mucosa, which causes an increase in the permeability of the intestinal wall, triggering the process of translocation of various bacteria from the intestinal tract to the blood circulation so that it can trigger septicemia and sepsis. Dadih or commonly known as ampiang dadih is a fermented buffalo milk product. Dadih contains lactic acid bacteria microbiota, which can function as probiotics fermented milk starter Lactococcus lactis D4 dadih to small intestine in obstructive jaundice in vivo. Methods: This study was an in vivo experimental study using 30 wistar rats, which were divided into 3 test groups. Observation of the condition of the small intestine was carried out histopathologically to assess the inflammatory process and the condition of the intestinal mucosa. Data analysis was performed using SPSS version 25 using univariate and bivariate methods. Results: Group 3 showed minimal histopathological inflammation compared to the control and was statistically different, p<0.05. Conclusion: Giving fermented milk starter Lactococcus lactis D4 dadih was able to reduce the inflammatory response and repair the intestinal mucosa in conditions of obstructive jaundice in vivo studies.